2022
DOI: 10.1371/journal.pgph.0000223
|View full text |Cite
|
Sign up to set email alerts
|

Association between knowledge of Human Immunodeficiency Virus transmission and consistent condom use among sexually active men in Nigeria: An analysis of 2018 Nigeria Demographic Health Survey

Abstract: An estimated 1.7 million people were living with HIV in Nigeria in 2020, with over 86,000 people newly infected. Although the global rates of HIV have remained consistent over time, Nigeria has the second-highest number of people living with HIV and contributes to 9% of the global burden of HIV/AIDS. This is due to several structural and individual-level factors that limit knowledge of HIV and condom utilization. In this context, this study examines the association between knowledge about HIV transmission and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 33 publications
5
18
2
Order By: Relevance
“…Consistent with our results, a recent study conducted among sexually active men in Nigeria 33 show that Open access knowledge of equally improved condom use. Another study conducted among South African married couples reported that females are less likely to use a condom if their male partner has refused to use a condom, 34 suggesting male dominance or power imbalance between women and men in condom negotiation.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our results, a recent study conducted among sexually active men in Nigeria 33 show that Open access knowledge of equally improved condom use. Another study conducted among South African married couples reported that females are less likely to use a condom if their male partner has refused to use a condom, 34 suggesting male dominance or power imbalance between women and men in condom negotiation.…”
Section: Discussionsupporting
confidence: 93%
“…More information on the broad DHS sampling pretest and methodology has been published elsewhere [7,24]. The survey is a recognised good source of the secondary dataset in SSA and has been utilised by various previous studies conducted in the region [7,[25][26][27][28][29]. We adopted the observational studies epidemiology guidelines in writing and reporting the findings from this study [30].…”
Section: Study Design and Data Sourcementioning
confidence: 99%
“…However, consistent condom use has been acknowledged as one of the most fundamental preventative measures against HIV acquisition and transmission [13]. In other recent studies, rates of consistent condom use have been shown to increase with higher levels of education and comprehensive sexual health education [15,17,66]. Approaches aimed at improving consistent condom use among young men should consider multi-level influences, including attitudes and decisions around condom use.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual risk behaviours such as having sex at an early age, having multiple sexual partners, having sex under the influence of alcohol or drugs, and having unprotected sex are welldocumented drivers for HIV and other STIs [12][13][14]. In addition, a lack of HIV knowledge and inconsistent condom use, especially among young people, significantly increase the risk of HIV transmission [15][16][17]. Efforts to increase knowledge of condom use and reduce HIV risks, as well as HIV testing, remain critical for young people.…”
Section: Introductionmentioning
confidence: 99%